THE INTERNALIZATION OF ISLAMIC EDUCATIONAL VALUES IN THE RUWAT BUMI TRADITION IN PURWONEGORO VILLAGE, PURWONEGORO DISTRICT, BANJARNEGARA REGENCY - Sri Mulyani; Muhamad Slamet Yahya (LP2M IAI Al-Khairat Pamekasan, 2026)
This study analyzes the internalization of Islamic educational values within the Ruwat Bumi tradition in Purwanegoro Village, Banjarnegara Regency. Using a qualitative ethnographic approach, the study reveals how Islamic educational values are internalized through cultural rituals. The results indicate that the Ruwat Bumi tradition successfully internalizes Islamic educational values through processes of transformation, transaction, and transinternalization of values. Collaboration between cultural and religious authorities creates a harmonious integration between local values and Islam. This tradition functions as an effective medium for non-formal education through an experiential learning approach. The research findings enrich the theory of the indigenization of Islam and offer a model of character education based on local wisdom.